Pengaruh Kebutuhan Konsumen Dan Kualitas Produk Terhadap Preferensi Belanja Pasar Tradisional Pesing Koneng di Jakarta Barat - Deril Prasetio Pasda Putra; Budi Santosa Kramadibrata (Jurnal Strategi Bisnis Teknologi, 2024)
Traditional markets and supermarkets offer unique shopping experiences. Changes in shopping patternsreflect the complexity of social and economic dynamics. This study aims to understand the impact of consumerneeds and product quality on shopping preferences in the traditional market of Pesing Koneng, West Jakarta,benefiting academics, practitioners, and policymakers. The study employs an associative quantitative approachwith 96 respondents and questionnaires as research instruments. The analysis results indicate a positive influenceof consumer needs and product quality on shopping preferences. It is important to note that this analysis wasconducted solely in one traditional market without considering other variables or moderators that could affectshopping preferences more comprehensively.